2019
DOI: 10.1186/s12877-019-1096-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes of upright body posture in the sagittal plane of men and women occurring with aging – a cross sectional study

Abstract: Background Body posture is a fundamental indicator for assessing health and quality of life, especially for elderly people. Deciphering the changes in body posture occurring with age is a current topic in the field of geriatrics. The aims of this study were to assess the parameters of standing body posture in the global sagittal plane and to determine the dynamics of changes in standing body posture occurring with age and differences between men and women. Methods The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 54 publications
2
43
0
1
Order By: Relevance
“…The distinctive hormonal balance in postmenopausal women 39 , 40 may lead to an increasing fat mass or rather changes in fat distribution 41 . Hormonal shifts with an increased androgen level, e.g., testosterone in comparison to estradiol may be linked to a lower fat percentage in the legs and an accumulation of abdominal and visceral fat 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The distinctive hormonal balance in postmenopausal women 39 , 40 may lead to an increasing fat mass or rather changes in fat distribution 41 . Hormonal shifts with an increased androgen level, e.g., testosterone in comparison to estradiol may be linked to a lower fat percentage in the legs and an accumulation of abdominal and visceral fat 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Differences between men and women in COP parameters are observed only in older people [4]. Recent studies indicate that these differences may depend on somatic changes during the period of involution [5]. In athletic training, special attention is paid to improving the ability to maintain and control body balance.…”
Section: Introductionmentioning
confidence: 99%
“…Boulay et al demonstrated excellent the intra-observer and inter-observer reliability of these measurements 15 . The C7 plumb line is another measurement useful in evaluating sagittal balance [16][17][18] . The horizontal distance between the posterior superior corner of the sacrum and the vertical reference line from the center of the C7 vertebra (C7 plumb line) is defined , and the sagittal balance is indicated by the distance 15,17,19 .…”
Section: Introductionmentioning
confidence: 99%